The Middle English Bible : a Reassessment. - Kelly, Henry Ansgar (Middle Ages series., 2016)
Translated shortly before 1400, the Bible became the most popular medieval book in English. Scholars call it the Wycliffite Bible, attributing it to followers of the heretic John Wyclif, and say that it was banned in 1407. Henry Ansgar Kelly disagrees, arguing that it was a nonpartisan effort, and never the object of any prohibition.